Development of Ecotourism based on Community Empowerment (a Case Study of Kebumen Regency) - Mafruhah, Izza; Mulyani, Nunung Sri; Istiqomah, Nurul; Ismoyowati, Dewi (Muhammadiyah University Press, 2018)
The main objective of this research is to formulate a participatory and inclusive model of economic development by optimizing the potential of local resources in Kebumen regency, Central Java, Indonesia by 1) identifying local resource-based economic potentials to be developed into pilot projects in regional development, 2) analyzing factors affecting the success of potential development, 3) analyzing the needs that influence the increase of community and stakeholders participation in regional development activities. This study uses Geographic Information System to map economic potential, Analytical Hierarchy Process to analyze factors that influence community participation, and ATLAS.ti to analyze needs and activities in developing leading sectors. The analysis shows that the economic potential in Kebumen district is focused on the potential of natural resources which include forestry, agriculture, fisheries, plantations and livestock. The regional development needs to be carried out thoroughly from upstream to downstream. AHP analysis shows that the factors that influence the success of potential development are internal, institutional and external factors. Needs analysis shows that the community holds an important role but must be supported by other stakeholders, namely the government, business actors and academics.This study recommends upstream-downstream development through nature-based ecotourism. The upstream sector that must be prepared is natural conservation combined with access to accessibility. The concept of back-to-nature developed in ecotourism must be supported by the provision of facilities and infrastructure that allows visitors to reach and enjoy the nature's beauty. In the downstream sector, tourism support services such as culinary and souvenir typical of Kebumen regency become an important part and need to involve all elements of community, especially those around the tourism destinations.